Position Paper on School Guidance Services: A Reaction - Morris, G. Barry; Savage, Hugh W. (Canadian Journal of Counselling and Psychotherapy, 2012)
This paper is a reaction to the position taken by the Canadian School Trustees' Association (1981) regarding school counselling services. The reaction investigates the reasons provided by the CSTA for this position. Included are an examination of the definition of Career Education, the concern for youth unemployment, and the orientation of counselling services suggested by the trustees. An implicit theme of the paper is recognized and used as a basis for recommending futuristically-oriented programs in schools.